Archetypes from Underground : Notes on the Dostoevskian Self - Harrison, Lonny Roy (Book collections on Project MUSE., 2016)
Archetypes from Underground: Notes on the Dostoevskian Self uncovers archetypal imagery in Dostoevsky s stories and novels and argues that archetypes bring a new dimension to our understanding and appreciation of his works. In this interdisciplinary study, Harrison analyzes selected texts in light of fresh research.